RANCANGAN PROTOTIPE MESIN PENGERING GABAH BERBASIS TEKNOLOGI HYBRID: Prototype Design of Grain Dryer Machine Based on Hybrid Technology - Prasetyo, Andre Ryan; Sulis Yulianto; Edi Widodo (Jurnal Konversi Energi dan Manufaktur, 2024)
Until now, the process of processing paddy into rice still relies heavily on the traditional and commonly used methods. During the drying stage, the harvested rice grains are spread out and sun dried. To address this issue, an effective solution is needed to enhance the quality of of rice seeds. Therefore, a post harvest rice handling technology is being developed with a hybrid technology based grain drying tool, where solar energy is still harnessed through photovoltaic solar panels (PLTS). The purpose of this research is to design, develop, and test a prototype grain drying machine abased on hybrid PLTS technology. The research focuses on calculating the power drying, and evaluating the PLTS system. The methods used include testing grain drying with variations in temperatures of 45ºC, 50ºC, dan 51ºC , as well as a grain weight of 8 kg. the greatest energy consumption during drying is directed towards the PLTS battery system, and calculations are performed to determine the duration of battery usage. The research findings reveal drying efficiencies of 9.7%, 12.8%, and 13.12% and final mouisture contents of 16.3%, 14.6% and 14.1 % at temperatures of 45ºC, 50ºC, and 51ºC respectively. The optimal drying times are 2 hours at 45ºC and 50ºC, and 1.5 hours at 51ºC. the battery usage time with a power of 209 W is 2.3 hours.